A very political philosophy of education: science fiction, schooling and social engineering in the life and work of H.G. Wells literary lives, political philosophies, public education - Gearon, L (Wiley, 2019)
This article argues that Wells’ science fiction and subsequent political engagements are a continuum expressed by an imperative: that human history is held ‘between education and catastrophe’. The life and work of a politically unfashionable but still popular writer of science fiction are also a masterclass in establishing the critical importance of the interface of literature and political philosophy in education. Drawing from archival work on the International PEN papers at the University of Texas at Austin, by way of specific application to one area of the curriculum, the article also makes a tentative methodological case for the exploration of literary archives, political lives and political philosophies.